Mapping the Literature on Financial Behavior: a Bibliometric Analysis Using the VOSviewer Program - Dubyna, M.; Popelo, O.; Kholiavko, N.; Zhavoronok, А.; Fedyshyn, M.; Yakushko, I. (WSEAS Transactions on Business and Economics, 2022)
The objective of the article is to study the current state of researches of financial behaviour. The article is conceptual and based on the use of the methodology of the bibliometric analysis. The analysis is based on data retrieved from functionalities of the Scopus and Web of Science platforms. The VOSviewer program is used for network visualization of keywords in scientific publications. Key findings are the number of publications directly study the nature and features of the financial behavior formation of various economic agents is insignificant, but is constantly growing. An important role in this process is played by digitalization processes of financial services, which have an important impact on the models transformation of both financial behavior of economic ag
Keywords: Financial Behaviour, VOSviewer, Bibliometric, Economic Agents, Households, Financial Services Market, Scopus, Web of Science Core Collection.